Alkaline hydrolysis of olive fruits wastes for the production of single cell protein by Candida lipolytica - Rages, Ashraf Anwar; Haider, Mustafa M.; Aydin, Miraç (Elsevier BV, 2021)
Abstract This study aims to investigate the probable production of single-cell protein (SCP) through an identified yeast Candida lipolytica 10 DSM 70561, SM-0301 through the hydro-alkaline decomposition of the olive residuals by the recycling of the olive fruit residues and its use as a carbonic source for yeast growth and to provide the ideal circumstance to gain highest quantity of Carbohydrate of the hydro-alkali product. Alternation of the physical and chemical factors of the nutritional media in order to obtain the highest rate of production. The ideal state of this hydro-decomposition was as follows: 0.8 M of sodium hydroxide, temperature at 100 °C and duration time of 60 min. This context provided the highest sugar production, i.e. up to 12.5%. The ideal growth of the yeast and production of SCP was after 4 days of incubation with a rotation speed of 150 RPM at 30 °C and initial pH value of 5.5. Moreover, the medium containing 0.4% peptone as a source was superiors than other used peptone concentration with respect to yeast growth (17.55 g/l) and SCP production (11.24 g/l).
Keywords: 2. Zero hunger